THE DISRUPTIVE FORCE OF 3D PRINTING ON SUPPLY CHAINS - Alexandra Ioana FLOREA IONESCU (Business Excellence and Management, 2015)
Considered by McKinsey one of the disruptive technologies that will change the way of manufacturing, 3D printing is a method widely used in design and prototyping. This method can have a great impact on the supply chain as soon as it will be used in manufacturing, as companies will be able to manufacture on their own and very quickly what is now realized by a wide series of subcontractors. This article has as its goal to discover if indeed 3D printing will very soon restructure the supply chains and in what way.